Implementation of Electronic Signatures and E-Notarization within the Indonesian Notarial Legal Framework - Markus Gunawan; Erniyanti Erniyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines the implementation of electronic signatures and e-notarization within Indonesia's notarial legal framework, analyzing the tensions between technological innovation and traditional notarial principles. Indonesia has established basic legal recognition for electronic signatures through Law No. 11/2008 on Electronic Information and Transactions (as amended by Law No. 19/2016) and conceptually acknowledged cyber notary in the explanation of Article 15(3) of Law No. 2/2014 on Notary Positions which mentions